Uma análise sobre os reflexos tributários e previdenciários do fenômeno da “pejotização” - Carlos, Amanda Pontes Nunes (Universidade Federal Rural do Semi-Árido, 2018)
Based on the phenomenon of "pejotização", the present research seeks to make considerations about the tax and social security implications of this contractual relationship model. Therefore, it is proposed to define the mentioned phenomenon and to demonstrate the different positions on the feasibility of its application, opening space to evaluate the causes that lead the worker to adhere it. Next, a case study based on a judgment made by the Administrative Council of Tax Appeals is made, aiming to know the fiscal perspective on the "pejotização" phenomenon. At the last moment, an attempt is made to undertake an analysis of the tax and social security consequences of a "pejota". As for the methodology, it consists of a bibliographical, documentary and legislative research, based on specialized doctrine on labor law, electronic publications and academic works, as well as in judicial and administrative decisions on the subject. In conclusion, the contracting of a legal entity constituted by a single owner reduces the tax and social charges owed by those involved, thus interfering with the collection of resources destined for tax revenue.
Artigo Acadêmico
Keywords: Flexibilização; Pejotização; Reflexos tributários e previdenciários; Flexibilization; Pejotização; Tax and social security reflexes; CIENCIAS SOCIAIS APLICADAS::DIREITO